Lateral diffusion of graphene oxides in water and the size effect on the orientation of dispersions and electrical conductivity. (December 2017) - Kim, Seo Gyun; Wang, Sang Hoon; Ok, Chang Min; Jeong, Seung Yol; Lee, Heon Sang
Abstract: We have measured the translational and rotational diffusion coefficients of graphene oxide (GO) sheets in water by using dynamic light scattering (DLS) and depolarized DLS. We show that the GO sheets in dilute regime translate laterally in such a way that rigid-rods move perpendicularly to their axis direction. This discovery renders a facile method for the determination of the average lateral size of GO sheets by using DLS with the simple rod-model. The lateral size ( L ) determined by DLS is 20.15, 3.65, 1.79, and 1.09 μ m for samples with ultra-sonication exposure times of 0, 3, 12, and 60 min, respectively. The L is correlated with the critical LC concentration and the electrical percolation threshold. The size dependency of the critical LC concentration follows the scaling of the Onsager model if and only if L ≤ 3.65 μm. In the reduced GO (rGO) coated films, the electrically conductive networks are two dimension in percolation scaling law when L ≥ 3.65 μm, but the higher fractal dimension when L ≤ 1.79 μm. In the films having 85% light transmittance, the surface resistivity is 6.2 kΩ/sq when L ≥ 3.65 μm, and 60 kΩ/sq when L ≤ 1.79 μm. Graphical abstract: